Genetic characterization and clinical implications of human papillomavirus type 16 (HPV16) variants from northeastern Argentina - Badano, Inés (2015)
Fil: Badano, Inés. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales. Laboratorio de Biología Molecular Aplicada; Argentina.